(untitled) (Journal of the College of Basic Education, 2023)
William Golding’s first novel, Lord of the Flies, published in 1954, is still widely considered as his major work. It is one of the most widely- read, widely- admired, and widely- discussed novels in the last few decades. Throughout the novel, he shows a consistent struggle between good and evil; goes in parallel with his pessimistic view of human nature and his optimistic aspect represented in the characters of Ralph, Piggy and Simon. This thesis makes Lord of the Flies one of those novels which can be given several interpretations and be subject to controversial, critical and analytical approaches. Some perceive a bleak picture of humanity offered in Lord of the Flies when the symbol of reason and common sense is forced into an outlaw existence, and evil is chasing it. While others celebrate the shining hope of Ralph’s rescue and see the sacrifices as a homage good humanity pays for reaching to a more mature and higher state of being. What is so interesting in this novel is Golding’s treatment of evil and his raising a subject of so much concern to the twentieth century people who have witnessed two horrible world wars. Such concerns were becoming the subject of critical controversies in popular and scholarly publications. The Struggle between Pessimism and Optimism in Lord of the Flies: Of the many great events of the 20th century, the two World Wars played a great and decisive role in forming new attitudes and opinions. William Golding was among the many writers whose lives were touched by the calamities and horrors of war, which left an unforgettable stamp on his literary career. The horrors of the World War 11 helped him to perceive some kind of innate human evil, like that explored in Lord of the Flies. Golding himself stated that "Lord of the Flies takes the supposed innocent experience of the island- like life in order to test it against the experience of Nazism and Second World War." 1 His work in the navy where he became a lieutenant and was placed in command of a rocket launching ship helped him to formulate this new vision about human nature. During that war, Golding learned how brutal people can be to one another, and witnessed all kinds of inhumanity and persecution